Concerning the stages of evolution of statehood - Gevorgyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The statehood is a complex system which comprises of not only the special institutions, rules (norms) ensuring the political life of the society, but also special phenomena of decisive nature, which have essential influence on both the social practice and the level of efficiency of the state and legal institutions. The scientific literature reflects an opinion concerning the three-stage scheme of evolution of the statehood, according to which the stages of the statehood are as follows: early statehood — the weakly centralized, politically organizing societies, the social and administrative-political structures whereof are not developed; developed statehood — the politically organizing societies of the Ancient World, the Middle Ages and the New Era, with the already centralized system, wherein the class system is already fledged; mature statehood — the politically organizing societies with the developed economic system and the advanced social structure, wherein the nations with representative democracy are fledged. 37 The stages of evolution of the statehood are first and foremost predetermined by the level of interrelation and interaction between the society and the authorities. The society belongs to where the power and the law stand. Any society is determined under the law, and lack of legal order makes it impossible. The mature state is the organic form of the political organization and of the economically, socially and culturally developed society. It is furnished with the system of bureaucratic and other special bodies, possesses a developed system of administration and the law, autonomy, developed mechanism of coercion and supervision, and ensures the progress and dynamics tendencies inside the society. The social institutions bring to formation of the social supervision over the relevant activities, as well as of certain frames limiting the activeness and initiative undesirable for the system. The social structure of the society may be deemed as a constant link between the elements comprising it. As a key element of the society, the social institution gives an individual the opportunity to hold a social position in the society — have a status and perform certain social functions, i.e. play a certain role in the society. The statehood that organizes the society and classifies it from the structural aspect, performs a vital function by creating the deontological area of the socium. The statehood, supported by its elements (the state power, the state, the state authorities, the law), moulds the models of the needed moral and legal line of conduct. The law and the politics, being organic elements of the statehood, practically cover all the areas of the society and the social existence.